The EP2 receptor is the predominant prostanoid receptor in the human ciliary muscle. - Matsuo, T (1993)
Prostaglandins can reduce intraocular pressure by increasing uveoscleral outflow. We have previously demonstrated that the human ciliary muscle was a zone of concentration for binding sites (receptors) for prostaglandin F2 alpha and for prostaglandin E2. Here, we try to elucidate the types of prostanoid receptors in the ciliary muscle using competitive ligand binding studies in human eye sections and computer assisted autoradiographic densitometry. Saturation binding curves showed that the human ciliary muscle had a large number of binding sites with a high affinity for prostaglandin E2 compared with prostaglandin D2 and F2 alpha. The binding of tritiated prostaglandin E2 and F2 alpha in the ciliary muscle was displaced most effectively by prostaglandin E2 and 11-deoxy prostaglandin E1 (a selective EP2 prostanoid receptor agonist), whereas the binding of prostaglandin D2 was displaced most effectively by prostaglandin E2 and D2. These results indicate that the dominant prostanoid receptor in the human ciliary muscle is the EP2 subclass and that there is also a small number of DP receptors.